Zbirka "Pietro Nobile" Državnog arhiva u Rijeci kao izvor za proučavanje izgleda istarskih naselja početkom XIX. stoljeća - Bradanović, Marijan (Annales. Series historia et sociologia, 2007)
This article contains an analysis of a collection of drawings representing motifs from Istria. They were drawn by the renowned architect Pietro Nobile from Trieste and are kept in the National Archives in Rijeka. The history of the collection is described - it had been discovered, bought and catalogued between the Two Wars by Camillo De Franceschi, a historian, librarian and archivist from Pula. After World War II the collection has been kept in the National Archives in Rijeka. The collection consists of 79 drawings of vistas and landscapes and three portraits. It was dated on the grounds of a contemporary inscription from the year 1815 on the portrait of canon Valčić from Brseč, yet some of the drawings were certainly created somewhat earlier. The drawings are marked by their sketchy and explicitly realistic manner, and differ from their contemporary depictions of Istrian towns, where realistic qualities were lost during subsequent treatment. Previously unknown details of the urban scheme of Istrian towns are described, which have been lost in the intervening period, including some, for which these drawings represent the only illustration. Like his predecessors Nobile too is primarily interested in documenting monuments from the Antiquity, yet his work exhibits a broader interest in antiques, an anticipation of the forthcoming period of Romanticism. Among the numerous vistas from Pula, providing a more precise set of information than any other source known so far, there is an outstanding depiction of the exterior side of the Golden Gate with a segment of the city walls and a tower in the northern direction. The vistas from Rovinj, including drawings of a part of the front façade of the St. Euphemia parish, a pedestal with side columns and the remains of the harbour quarantine on the Rovinj waterfront are of special interest. The drawing of the main town squarein Koper, including a detail of the façade of the Armeria building and one of the original front façade of the church of St. Peter in Piran are noteworthy as well. Among the motifs from Poreč the forum temple stands out and an illustration of its back façade with Medieval walls in the elevation is considered to be a rarity. Vistas from rarely depicted towns represent an even more valuable source of information, especially the drawing with a fortified causeway in front of the inner town walls of Umag and the drawings of the main entrance to Labin and Tinjan depicting a tower with a passage, erected over the main city entrance. The towns Bale, Plomin, Motovun, Svetvinčenat and the castels in Payin and Lupoglav have been found to remain virtually unchanged. The veracity of depictions is proven by a parallel survey of available graphic art material and through field research. Apart from possessing great artistic value this collection represents one of the most comprehensive graphic art sources of information concerning old Istrian towns from the first half of the 19th century. Despite this fact it has only received modest attention of researchers, so let this be a reminder and an appeal for further comparative analysis of the drawings and evaluation of architectural and conservational endeavours of Pietro Nobile in Istria
Keywords: architecture; arhitektura; Istra; Istria; Nobile, Pietro, 1776-1854; primary source; risbe; urbanism; urbanizem; vedute; zgodovinski viri